Live Longer and Healthier: Impact of Pension Income for Low-Income Retirees - Chiara Malavasi; Han Ye (Institute of Labor Economics (IZA), 2024)
We estimate the effect of additional pension income on mortality outcomes by exploring the eli- gibility criteria of a German program subsidizing the pensions of low-wage workers. Using novel administrative data, we find that eligibility leads to a 2-month delay in age at death (censored at 75). Survey evidence suggests that additional pension income improves both mental and physical health. In addition, individuals feel less financially constrained and are more optimistic about their future. Heterogeneity analysis indicates that the results are mainly driven by men.
Keywords: I10; I12; J14; J26; 330; mortality; health; income; pension subsidy; retirement